2007
DOI: 10.1103/physrevb.76.205316
|View full text |Cite
|
Sign up to set email alerts
|

Definitive evidence of interlayer coupling betweenGa1xMnxAslayers separated by a nonmagnetic spacer

Abstract: We have used polarized neutron reflectometry to study the structural and magnetic properties of the individual layers in a series of Al y Be z Ga 1-y-z As/Ga 1-x Mn x As/GaAs/ Ga 1-x Mn x As multilayer samples. Structurally, we observe that the samples are virtually identical except for the GaAs spacer thickness (which varies from 3-12 nm), and confirm that the spacers contain little or no Mn. Magnetically, we observe that for the sample with the thickest spacer layer, modulation doping by the Al y Be z Ga 1-y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…tization parallel to H, [25]. which can be model-tted using exact dynamical calculations [26] to determine the actual magnetizations of the individual GaMnAs layers within the trilayer structure [10].…”
Section: Magnetization Results Observed Onmentioning
confidence: 99%
See 1 more Smart Citation
“…tization parallel to H, [25]. which can be model-tted using exact dynamical calculations [26] to determine the actual magnetizations of the individual GaMnAs layers within the trilayer structure [10].…”
Section: Magnetization Results Observed Onmentioning
confidence: 99%
“…Theoretical models predict both ferromagnetic (FM) and antiferromagnetic (AFM) interactions between the FMS layers, the type of inter-layer exchange coupling (IEC) being of course crucial to the device operation [58]. It has been shown in a number of studies that the type of IEC whether it is FM or AFM depends sensitively on the thickness and doping of the non-FM spacers between the FM layers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier observations of AFM IEC in semiconducting ferromagnets were reported in rare-earth-based semiconductors, such as EuS/PbS or EuS/YbSe, in which the Curie temperatures (T C ) are as low as 18 K. 7,8 In structures involving diluted magnetic semiconductors (DMSs) such as GaMnAs, in which the T C can reach as high as 170 K by the careful optimization of engineering parameters, [9][10][11] only the FM IEC has been observed for a long time. [12][13][14][15][16] Part of the reason for this may be that it is very difficult to adequately describe and predict the properties of these DMS systems in theoretical calculations. In principle, magnetic interactions in DMSs are expected to possess similar characteristics as in the metallic systems based on the RKKY mechanism.…”
mentioning
confidence: 99%
“…Short-period superlattices formed the basis of neutron reflectivity studies of Szuszkiewicz et al 17 , who confirmed the ferromagneticonly interlayer coupling (mainly for 6 ML spacer). In the work of Kirby et al 18 neutron reflectometry and magnetization curve studies of trilayer structures were performed, in which the magnetization of top and bottom layer has been resolved. This indicated distinct ferromagnetic coupling through a spacer of large thickness (about 20 ML).…”
mentioning
confidence: 99%